Markers of deep infiltrating endometriosis in patients with ovarian endometrioma: a predictive model. (February 2017) - Perelló, Maria; Martínez-Zamora, Maria A.; Torres, Ximena; Munrós, Jordina; Llecha, Silvia; De Lazzari, Elisa; Balasch, Juan; Carmona, Francisco
Abstract: Objective: The purpose of the study was to develop an easily applicable predictive model to predict deep infiltrating endometriosis in patients with ovarian endometrioma. Study design: We performed a retrospective analysis of 178 consecutive women with ovarian endometrioma who underwent surgery, with histological confirmation and complete removal of endometriosis in the Hospital Clinic of Barcelona. Several markers were prospectively obtained and compared between the group of patients presenting deep infiltrating endometriosis associated with ovarian endometrioma and women with only ovarian endometrioma. Multiple logistic regression analysis was performed to create a model to predict the presence of deep infiltrating endometriosis and internal validation was later performed. Results: Of the 178 patients studied, 80 (45%) were classified in the ovarian endometrioma group and 98 (55%) in the group of patients presenting deep infiltrating endometriosis associated with ovarian endometrioma. The independent variables to predict deep infiltrating endometriosis were: at least one previous pregnancy, a past history of surgery for endometriosis and the mean endometriosis-associated pelvic pain score. The area under the ROC curve was 0.91 (95% confidence interval: 0.86–0.94), with an optimal cut-off of the predicted probability of 0.54. The sensitivity of the model was 80% and the specificity 84%. Conclusions: This model predicts the development of deep infiltrating endometriosis in patients with ovarian endometriomas allowing prioritization of women for referral to specialized centers.